The Exploration of the Site known as the Kirk Stones of Stroupster, in the Parish of Wick, County of Caithness (Proceedings of the Society of Antiquaries of Scotland, 1916)
Four rectangular stone structures are surrounded by a roughly circular stone wall. The structures have passageways leading into them and internal features including hearths and possible benches or beds. A few small fragments of wheel-thrown pottery and limpet shells were found.